Coiled coil type neoglycoproteins presenting three lactose residues. Issue 13 (30th March 2016) - Sweeney, Sinclair M.; Bullen, Gemma A.; Gillis, Richard B.; Adams, Gary G.; Rowe, Arthur J.; Harding, Stephen E.; Tucker, James H.R.; Peacock, Anna F.A.; Murphy, Paul V.
Graphical abstract: Abstract: Scaffold design, synthesis and application are relevant for biomedical research. For example, multivalent interactions, such as those between cell surface glycoproteins and lectins can influence the potency and duration of signalling. The spacing between carbohydrates on their native protein scaffold could be important. Herein, the coiled coil design principle is used to generate synthetic coiled coil type glycoproteins, where three lactose residues are grafted to the coil via N-linkages to asparagine. Molecular modelling indicates that the distance between the galactose anomeric carbon atoms on the neoglycoproteins is ∼30 Å. The inclusion of lactose was accommodated in both the final heptad towards the N-terminus, or more centrally in the penultimate heptad. In either case, neither the helicity nor the assembly to the trimeric form was unduly altered by the presence of the disaccharide.